Illuminating Neuropeptide Y Y4 Receptor Binding: Fluorescent Cyclic Peptides with Subnanomolar Binding Affinity as Novel Molecular Tools - Gleixner, Jakob; Kopanchuk, Sergei; Grätz, Lukas; Tahk, Maris Johanna; Laasfeld, Tõnis; Veikšina, Santa; Höring, Carina; Gattor, Albert O.; Humphrys, Laura J.; Müller, Christoph; Archipowa, Nataliya; Köckenberger, Johannes; et al. (ACS Pharmacology & Translational Science, 2024)
The neuropeptide Y (NPY) Y4 receptor (Y4R), a member of the family of NPY receptors, is physiologically activated by the linear 36-amino acid peptide pancreatic polypeptide (PP). The Y4R is involved in the regulation of various biological processes, most importantly pancreatic secretion, gastrointestinal motility, and regulation of food intake. So far, Y4R binding affinities have been mostly studied in radiochemical binding assays. Except for a few fluorescently labeled PP derivatives, fluorescence-tagged Y4R ligands with high affinity have not been reported. Here, we introduce differently fluorescence-labeled (Sulfo-Cy5, Cy3B, Py-1, Py-5) Y4R ligands derived from recently reported cyclic hexapeptides showing picomolar Y4R binding affinity. With pKi values of 9.22-9.71 (radioligand competition binding assay), all fluorescent ligands (16-19) showed excellent Y4R affinity. Y4R saturation binding, binding kinetics, and competition binding with reference ligands were studied using different fluorescence-based methods: flow cytometry (Sulfo-Cy5, Cy3B, and Py-1 label), fluorescence anisotropy (Cy3B label), and NanoBRET (Cy3B label) binding assays. These experiments confirmed the high binding affinity to Y4R (equilibrium pKd: 9.02-9.9) and proved the applicability of the probes for fluorescence-based Y4R competition binding studies and imaging techniques such as single-receptor molecule tracking.
CRIS-Team Scopus Importer:2024-03-29
Keywords: binding assay; fluorescence microscopy; fluorescent ligand; neuropeptide Y; pancreatic polypeptide; Y